GOOD GOVERNANCE DAN KUALITAS LAPORAN KEUANGAN PEMERINTAH: SUATU KAJIAN DI PEMERINTAH DAERAH PROVINSI JAMBI - Masnun, Masnun (Ekonomis: Journal of Economics and Business, 2018)
Good governance is essential and inseparable for every entity today. Good governance becomes one of the foundations in decision making for stakeholders to assess the performance of government both at the central and in the region. This study uses descriptive analysis method to see whether the implementation of good governance can be assessed in terms of quality of local government financial statements that have been audited by BPK and what is the cause of the lack of good governance of government finance. The analysis uses opinion data issued by the auditor on the Jambi Province government financial report and the results of the previous research analysis. Based on the analysis concluded that good governance can be assessed by looking at the quality of local government financial statements (LKPD) as measured from the auditor's opinion. While the lack of good governance of local government finances due to the low quality of human resources in local government and the application of government accounting standards that have not been maximized.Key words : Good governance,Â  Local government financial statements